Patch work : a life amongst clothes - Wilcox, Claire (Bloomsbury Publishing, 2020)
Claire Wilcox has been a curator of fashion at the Victoria and Albert Museum for most of her working life. In Patch Work, she steps into the archive of memory, deftly stitching together her dedicated study of fashion with the story of her own life lived in and through clothes. From her mother's black wedding suit to the swirling patterns of her own silk kimono, her memoir unfolds in spare, luminous prose the spellbinding power of the things we wear. In a series of intimate and compelling close-ups, Wilcox tugs on the threads that make up the fabric of our lives: a cardigan worn by a child, a mother's button box, the draping of a curtain, a pair of cycling shorts, a roll of lace, a pin hidden in a seam. Through the eye of a curator, we see how the stories and the secrets of clothes measure out the passage of time, our gains and losses, and the way we use them to unravel and write our histories.